1996
DOI: 10.1007/bf00200659
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of multinucleated giant cell apoptosis in foreign-body granuloma

Abstract: To elucidate the role of apoptosis in the disappearance of multinucleated giant cells from the granulation tissue in cases of foreign-body granuloma, we induced a foreign-body reaction by implanting a collagen sponge into the dorsum of the rat and observed apoptotic changes within the multinucleated giant cells using electron microscopy. Two types of multinucleated giant cells were identified presenting apoptotic characteristics morphologically. One was characterized by apoptosis of only one nucleus, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Numerous previous studies have investigated the biological phenomenon of apoptosis, 26,44,45 but the occurrence of apoptosis or cell necrosis in relation to implanted biomaterials is addressed only in a few studies. Honma and Hanasaki 46 described the occur- The reactive capsule at the smooth surface appeared thicker than that of the coarse surface at all time intervals, and this difference became significant after 12 weeks of implantation (p = 0.0296; reactive capsule data from Rosengren et al 34 ). The number of PI-positive cells showed a statistically significant positive correlation to the capsule thickness at 6 weeks (p = 0.0305).…”
Section: Discussionmentioning
confidence: 85%
“…Numerous previous studies have investigated the biological phenomenon of apoptosis, 26,44,45 but the occurrence of apoptosis or cell necrosis in relation to implanted biomaterials is addressed only in a few studies. Honma and Hanasaki 46 described the occur- The reactive capsule at the smooth surface appeared thicker than that of the coarse surface at all time intervals, and this difference became significant after 12 weeks of implantation (p = 0.0296; reactive capsule data from Rosengren et al 34 ). The number of PI-positive cells showed a statistically significant positive correlation to the capsule thickness at 6 weeks (p = 0.0305).…”
Section: Discussionmentioning
confidence: 85%
“…These findings indicate that not all nuclei of multinucleated odontoclasts in apoptosis show a similar appearance of DNA degeneration. Honma and Hamasaki (1996) have reported that multinucleated giant cells in foreign-body glanuloma show differences in the apoptotic changes occurring in individual nuclei. Watanabe et al (2000) observed rabbit odontoclastic apoptosis induced by bisphosphonate administration and speculated that the degeneration of nuclei may not be synchronous but occur independently in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to apoptosis, necrosis is considered to be a nonspecific mode of cell death. Necrotic death is accompanied by the efflux of ions and water resulting in the rupture of the cytoplasmic and nuclear membranes, swelling of the mitochondria, and flocculation of the chromatin [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is important in the development of pulmonary disease [8,21]. Because the endothelium is not considered to be a rapidly renewing tissue, apoptosis of endothelial cells can lead to lung injury.…”
Section: Electron Microscopic Findingsmentioning
confidence: 99%